A 2018 Reference Guide to the Banff Classification of Renal Allograft Pathology. Issue 11 (November 2018) - Roufosse, Candice; Simmonds, Naomi; Clahsen-van Groningen, Marian; Haas, Mark; Henriksen, Kammi J.; Horsfield, Catherine; Loupy, Alexandre; Mengel, Michael; Perkowska-Ptasińska, Agnieszka; Rabant, Marion; Racusen, Lorraine C.; Solez, Kim; et al.
Abstract : Abstract: The Banff Classification of Allograft Pathology is an international consensus classification for the reporting of biopsies from solid organ transplants. Since its initial conception in 1991 for renal transplants, it has undergone review every 2 years, with attendant updated publications. The rapid expansion of knowledge in the field has led to numerous revisions of the classification. The resultant dispersal of relevant content makes it difficult for novices and experienced pathologists to faithfully apply the classification in routine diagnostic work and in clinical trials. This review shall provide a complete and simple illustrated reference guide of the Banff Classification of Kidney Allograft Pathology based on all publications including the 2017 update. It is intended as a concise desktop reference for pathologists and clinicians, providing definitions, Banff Lesion Scores and Banff Diagnostic Categories. An online website reference guide hosted by the Banff Foundation for Allograft Pathology (www.banfffoundation.org ) is being developed, which will be updated with future refinement of the Banff Classification from 2019 onward. Abstract : The Banff classification is the gold standard in kidney transplantation for both pathologists and clinicians. As this classification is evolving quickly, the authors provide a complete and simple illustrated reference guide to help everyone taking advantage of this growing piece of knowledge. Supplemental digital content is available in the text.